Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Roti Menggunakan Metode Promotion Mix Dan AHP (Studi Kasus Pada UMKM X Bakery Balikpapan) - Nur Ni'ma Maula Febriyanti; Vridayani Anggi Leksono; Sigit Rahmat Rizalmi; Mochamad Sulaiman (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2023)
The success of a business venture in marketing the products offered can be influenced by marketing strategy planning. Planning the right marketing strategy can help business actors to achieve sales targets. The purpose of this research is to find out, provide, and implement a new marketing strategy recommendation for bread X Bakery Balikpapan. So that the sales results increased by 5% from the implementation of Â implementation of the new marketing strategy. This study uses a questionnaire target of 70 respondents who come from the owners of bread X Bakery Balikpapan, distributors of bread X Bakery Balikpapan, and consumers of bread X Bakery Balikpapan. The analysis used is the Analytical Hierarchy Process (AHP) analysis. Promotion Mix is used as a method to analyze the marketing components that will be used as a new marketing strategy. Meanwhile, AHP is used as a decision-making method in selecting a new marketing strategy. Promotion Mix components used as criteria are advertising (0.314), sales promotion (0.302), personal selling (0.195), and public relations (0.189). Each Promotion Mix criteria has its own sub-criteria. The alternatives used are bread marketing through the distribution of brochures (0.147) and bread marketing through social media (0.853). The new marketing strategy for bread X Bakery Balikpapan is based on the Promotion Mix priority component with the highest weight value, namely the marketing of bread through social media (Instagram).